ժամանակակից թուրքերենի արմատական կրկնությունների տեսակները - Դիանա Հայրապետյան (ՀՀ ԳԱԱ հրատ.)
In this article we have tried to present phonetic and structual manifestations one of the most productive types of word formation in modem Turkish language , which is root repetition. In modem Turkish root repetition is formed through full, transformed or partial reduplications.
Keywords: Philology; Linguistics; Language and Literature